2020
DOI: 10.1016/j.omtn.2020.08.009
|View full text |Cite
|
Sign up to set email alerts
|

METTL14 Gene Polymorphisms Confer Neuroblastoma Susceptibility: An Eight-Center Case-Control Study

Abstract: Neuroblastoma is the primary cause of cancer death in childhood. METTL14 is tightly linked to cancer. However, whether single-nucleotide polymorphisms (SNPs) in the METTL14 gene could predispose to neuroblastoma susceptibility lacks evidence. With an epidemiology case-control study, associations between METTL14 gene SNPs and overall risk for neuroblastoma were estimated in 898 cases and 1,734 controls. Following that, stratified analysis was performed. Among the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 54 publications
(53 reference statements)
0
47
0
Order By: Relevance
“…The present and previous results (21) indicate that C282Y HFE impacts neuroblastoma characteristics such as therapy resistance and cell proliferation. Several studies reported that single nucleotide polymorphisms (SNPs) in genes [e.g., ATP binding cassette subfamily C member 1 (ABCC1); caspase 8 (CASP8); ERCC excision repair 1, endonuclease non-catalytic subunit/ERCC excision repair 4, endonuclease non-catalytic subunit (ERCC1/XPF or ERCC1/ERCC4); poly(ADP-ribose) polymerase 1 (PARP1); base excision repair (BER); methyltransferase like 14 (METTL14)] are risk factors for neuroblastoma development and patient survival (40)(41)(42)(43)(44)(45). Our data indicate that the frequency of the C282Y HFE SNP in neuroblastoma patients should also be determined in future clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…The present and previous results (21) indicate that C282Y HFE impacts neuroblastoma characteristics such as therapy resistance and cell proliferation. Several studies reported that single nucleotide polymorphisms (SNPs) in genes [e.g., ATP binding cassette subfamily C member 1 (ABCC1); caspase 8 (CASP8); ERCC excision repair 1, endonuclease non-catalytic subunit/ERCC excision repair 4, endonuclease non-catalytic subunit (ERCC1/XPF or ERCC1/ERCC4); poly(ADP-ribose) polymerase 1 (PARP1); base excision repair (BER); methyltransferase like 14 (METTL14)] are risk factors for neuroblastoma development and patient survival (40)(41)(42)(43)(44)(45). Our data indicate that the frequency of the C282Y HFE SNP in neuroblastoma patients should also be determined in future clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Odds ratios (ORs) and 95% confidence interval (CI) adjusted age were calculated, and haplotype frequencies were estimated using PLINK software. False-positive report probability (FPRP) analysis was used to evaluate the noteworthy associations of the significant findings ( 18 , 19 ). We set 0.2 as the FPRP threshold and assigned a prior probability of 0.1 for an association with genotypes under investigation.…”
Section: Methodsmentioning
confidence: 99%
“…M 6 A RNA modification has also been associated with other brain cancers such as neuroblastoma. Zhuo et al identified several SNPs in the gene encoding METTL14 , which may be associated with a predisposition to neuroblastoma development in a Chinese population ( Zhuo et al, 2020 ). Moreover, m 6 A and associated proteins may also represent potential biomarkers of various brain cancers including neuroblastoma.…”
Section: A In Brain Disordersmentioning
confidence: 99%